Colonial Monasticism, the Politics of Patronage, and the Beginnings of Gothic in Ireland: The Victorine Cathedral Priory of Newtown Trim, Co. Meath - Carey Bates, Rhiannon; O’Keeffe, Tadhg (Journal of Medieval Monastic Studies, 2017)
Abstract Small relative to its importance as the capital of the Anglo-Norman lordship of Meath, the medieval town of Trim was home to communities of canons regular and mendicants, and among the former were Victorine canons who served as the chapter of a cathedral that was newly-built just outside the town at the start of the thirteenth century. This paper presents a discussion of monastic observance in Trim before and after the Anglo-Norman invasion of Ireland in 1169, and an exploration of the context of the foundation of the Victorine priory and its cathedral church. It is argued that the Victorine church, one of the first Gothic buildings in Ireland, offers us a glimpse of what was possibly the earliest work of Gothic architecture in Ireland, a now-demolished Victorine house in Dublin.